Blake's Design of Mechanical Joints - Josephs, Harold; Huston, Ronald L., 1937- (Boca Raton, FL : CRC Press, 2017)
"Blake's Design of Mechanical Joints, Second Edition, is an updated revision of Alexander Blake's authoritative book on mechanical joint and fastener design. This revision brings Blake's 1985 volume up-to-date with modern developments in joint design, and recent technological advances in metallic and non-metallic materials, and in adhesive joining technologies. The book retains Blake's lucid, readable style and his balance of basic concepts with practical applications. Coverage of statistical methods, computational software usage, extensive examples, and a full glossary have been added to make the new edition a comprehensive, practical sourcebook for today's mechanical design engineers."--Provided by publisher.
4.13 Testing Variances from Two Populations: Use of the F-Distribution4.14 Design Studies of Variances; 4.14.1 Design Study 4.13; 4.14.2 Design Study 4.14; 4.14.3 Design Study 4.15; 4.14.4 Design Study 4.16; 4.15 Control Charts; 4.16 Design Study for Control Charts; 4.16.1 Design Study 4.17; References; Symbols; Chapter 5 Riveted and Bolted Joints; 5.1 Basic Formulas for Rivets; 5.2 Formulas for Eccentric Shear; 5.3 Performance of Riveted Joints; 5.4 Rigid Bolted Connections; 5.5 Gasket Effects; 5.6 Stiffness of a Flange in Compression; 5.7 Conventional Diagram for the Bolt Preload
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY & ENGINEERING -- Mechanical; TECHNOLOGY & ENGINEERING -- Industrial Design -- General; Joints (Engineering); SCIENCE / Mechanics / General; TECHNOLOGY / Engineering / Mechanical; TECHNOLOGY / Industrial Design / General